Involvement of metabotropic glutamate receptor 5 in pudendal inhibition of nociceptive bladder activity in cats - Larson, Jeffrey A (Blackwell Science Inc, 2011)
ABSTRACT: This study used MTEP, a metabotropic glutamate receptor 5 (mGluR5) antagonist, to examine the role of mGluR5 in the neural control of the urinary bladder and in the inhibition of the micturition reflex by pudendal nerve stimulation (PNS). Experiments were conducted in 11 female cats under α-chloralose anaesthesia when the bladder was infused with either saline or 0.25% acetic acid (AA). AA irritated the bladder, induced bladder overactivity and significantly (P< 0.001) reduced bladder capacity to 14.9 ± 10.3% of the saline control capacity. MTEP (0.1–50 mg kg(−1), i.v.) significantly (P< 0.05) increased bladder capacity during saline distension but not during AA irritation. However, MTEP induced a transient inhibition of isovolumetric bladder contractions under both conditions. PNS (5 Hz), which was tested at the threshold (T) intensity for inducing a complete inhibition of isovolumetric bladder contractions and at an intensity of 3–4T, suppressed AA-induced bladder overactivity and significantly increased bladder capacity to 68.0 ± 31.3% at 1T(P< 0.05) and 98.5 ± 55.3% at 3–4T(P< 0.01) of the saline control capacity. MTEP dose dependently (0.1–50 mg kg(−1), i.v.) suppressed PNS inhibition of bladder overactivity at low intensity (1T) but not at high intensity (3–4T). During saline infusion PNS significantly (P< 0.05) increased bladder capacity to 167.7 ± 27.1% at 1Tand 196.0 ± 37.4% at 3–4T. These inhibitory effects were not observed after MTEP (0.1–50 mg kg(−1), i.v.) which also increased bladder capacity. These results indicate that glutamic acid has a transmitter function in bladder and somato-bladder reflex mechanisms and raise the possibility that mGluR5 may be a target for pharmacological treatment of lower urinary tract disorders.